(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of this study was to model the metallic port which included samarium cobalt magnet in breast tissue expanders and to improve the accuracy of dose calculations with nanoDot optically stimulated luminescence dosimeter (nanoDot OSLD) measurements.Material and Methods: Mentor TTE (Temporary Tissue expander) (at a depth of 3 cm) was modeled by DOSXYZnrc Monte Carlo code and the nanoDot OSLD were used for dose measurements in solid water phantoms.Results: In present study, dose increases in tissue at 3 cm due to the backscatter of electrons was 16.3% for metallic port at 6 MV using the Monte Carlo method. It was observed 12 % in the experimental results. Additionally, while the decrease in dose behind the port was 17.4 % by Monte Carlo program code, it was observed 25.8 % in the experimental results Conclusions: In present study, the low dose region remains in saline solution within the tissue expander. It can be negligible clinically. In a clinical setting, the breast patients are treated with tangent beam fields. It was thought that unless the frontal direct field was not used in clinics for these patients, the dose reduction and dose increase would not do not play a role in influencing the treatment.